Psychological impact and mental health effect of COVID-19 among Jordanian population - Qasem , Nuha; Al-Ali, Mahmoud; Sanwar , Mohammad; Aquily , Mohammad (Jordan Medical Journal, 2022)
Background During public health emergencies, the major efforts of policy makers are directed towards physical and medical consequences, and little is directed towards the psychological impact of these outbreaks. Aim To assess the psychological impact and mental health effects of the current pandemic of Corona virus (COVID 19) on the general population in Jordan. Methodology A cross-sectional study was conducted using an online survey directed towards the general population in Jordan during the period March 25th to April 2nd, 2020. Mental health effect was measured using the Arabic version of the Depression, Anxiety and Stress Scale (DASS-21), while the psychological impact was measured using questions from the Arabic version of the Impact of Event Scale-Revised (IES-R). Total number of respondents was 1946. Results The levels of depression, anxiety and stress as measured by DASS-21 questionnaire showed that 13% had severe depression, 10% had severe anxiety, and 6.3% had severe stress. There was more psychological impact compared with mental health effects on the study population, as more than quarter of the sample (26.7%) reported severe psychological impact (score >38). Factors associated with higher psychological impact and mental health effects include younger age group, being female, childless, living in the remote areas, being a bachelor’s degree student or graduate, having low monthly income and having physical symptoms in the 14 days prior to the study. Conclusion Findings of this study can inspire health projects at the national level to better deal with these psychological issues in response to the current or any future health emergencies in Jordan.